FRI0430 Association Between Circulating Macrophage Migration Inhibitory Factor (MIF) with Adipokines Levels, Auto-Antibodies and Pro-Inflammatory Cytokines in Lupus Nephritis. (9th June 2015) - Diaz Rizo, V.; Fajardo Robledo, N.S.; Murillo Vazquez, J.D.; Perez Guerrero, E.; Trujillo, X.; Gonzalez Lopez, L.; Gamez Nava, J.I.
Abstract : Background: Macrophage migration inhibitory factor (MIF) is a cytokine that has a role in systemic lupus systemic lupus erythematosus (SLE) 1 . Elevated MIF levels have been observed in glomerulonephritis 2 . Some adipokines have shown proinflammatory properties in connective tissue diseases. MIF and some adipokines could be independent biomarkers for specific organ involvement in SLE, so it is required to evaluate the correlation with disease characteristics and autoantibodies. Objectives: To evaluate the correlation between MIF, adipokines, proinflammatory cytokines, autoantibodies and clinical variables in patients with proteinuria secondary to lupus nephritis. Methods: One hundred and thirty women with SLE were included in a cross-sectional study. Patients were classified in two groups: SLE with proteinuria (≥0.5g/vol/24 hours) (n=34) and SLE without nephritis (n=96). Assessment included disease activity score (m-SLEDAI), SLICC/ACR, clinical characteristics of kidney involvement (proteinuria, serum creatinine, creatinine clearance), characteristics of other organs involved and anthropometric assessment included body mass index (BMI). Serum levels of adipokines (leptin, adiponectin, resistin), and pro-inflammatory cytokines (MIF, TNF-α, IL-6) were quantified by ELISA. Also, we quantified anti-DNA, anti-nucleosome antibodies, C3 and C4. Results: In the comparison between SLE with proteinuria versus SLE without nephritis, there were no statistically significant differences in age, weight or BMI. Serum leptin, adiponectin, resistin were not statistically different between both groups (p=not significant). Anti-nucleosome antibodies titers were significantly higher in SLE with proteinuria versus SLE without nephritis (69.9±91.3 vs 18.1±47.7, p=0.038). MIF serum levels were higher in patients with active disease versus patients with inactive disease (13.0±8.7 vs 9.4±5.3, p=0.011), similarly anti-nucleosome antibodies titers were higher in patients with disease activity (59.2±87.9 vs 9.6±16.3, p=0.009). Negative correlation of MIF with age (r=-0.176, p=0.045) and a positive correlation with serum creatinine (r=0.675, p=0.008). There was no correlation between adipokines and cytokines in SLE. No correlation observed between circulating MIF with leptin/BMI (r=0.148, p=0.093), adiponectin (r=-0.028, p=0.753), resistin(r=0.129, p=0.186), TNF-α (r=0.002, p=0.987) or IL-6 (r=0.066, p=0.483), supporting that MIF levels are independent biomarker for organ involvement. Conclusions: MIF serum levels constitute an independent biomarker in SLE for disease activity and increasing creatinine in patients with nephritis. Our observation supports that circulating MIF has no correlation with adipokines and other pro-inflammatory cytokines in SLE, remarking the requirement of follow-up studies to evaluate the circulating MIF as predictor of relapses in SLE. References: Sreih A, et al. Arthritis Rheum. 2011;63:3942-51. Lan HY, et al. Kidney Int. 2000;57:499-509. Acknowledgements: Founding: This project was supported by the Fondo de Investigaciόn en Salud del Instituto Mexicano del Seguro Social: FIS/IMSS/PROT/G12/1135. Disclosure of Interest: None declared